Discrepancy between ionopause and photoelectron boundary determined from Mars Express measurements. Issue 23 (11th December 2014) - Han, X.; Fraenz, M.; Dubinin, E.; Wei, Y.; Andrews, D. J.; Wan, W.; He, M.; Rong, Z. J.; Chai, L.; Zhong, J.; Li, K.; Barabash, S.
Abstract: The Martian ionosphere directly interacts with the solar wind due to lack of a significant intrinsic magnetic field, and an interface is formed in between. The interface is usually recognized by two kinds of indicators: the ionopause identified from ionospheric density profiles and the photoelectron boundary (PEB) determined from the electron energy spectrum at higher energies. However, the difference between them remains unclear. We have determined the locations of crossings of the ionopause and PEB from Mars Express observations during 2005–2013 and found that the average position of the PEB appears to be 200 km higher than that of the ionopause, which corresponds to 10 3 cm –3 in the electron density profile. The discrepancy can be explained by cross‐field transport of photoelectrons. Key Points: The average altitude of the PEB is 200 km higher than that of the ionopause The discrepancy can be explained by cross-field transport of photoelectrons Both the Martian ionopause and PEB heights depend slightly on the SZA